Biology teaching: Challenges and contemporary perspectives (Research, Society and Development, 2025)
This study aimed to analyze the main challenges faced in Biology teaching in the contemporary context, considering pedagogical, curricular, technological, and social aspects, and to discuss perspectives and proposals that contribute to improving teaching practices and student learning. This study was a qualitative bibliographic study. Data collection was conducted through systematic searches in academic databases such as SciELO, Google Scholar, Redalyc, and the CAPES Journal Portal. Biology teaching plays an essential role in developing individuals who are aware, critical, and committed to social, environmental, and scientific issues. In the contemporary context, teaching Biology requires pedagogical practices that encourage knowledge construction, understanding of biological processes, and ethical reflection on the use of science. Among the main challenges faced are the lack of adequate infrastructure, the absence of laboratories, excessive content in curricula, and the lack of continuing education for teachers. These factors limit the adoption of more effective methodologies. On the other hand, incorporating contemporary themes makes teaching more contextualized and meaningful, bringing the academic content closer to students' realities. Furthermore, active methodologies and digital resources, when used, can promote engagement and learning. Therefore, it is essential to invest in teacher training, value the teaching profession, and promote public policies that ensure better teaching conditions. Overcoming challenges and exploring new possibilities are fundamental steps toward consolidating a more critical, contextualized, and transformative biological education.